Electrolyte additive, electrolyte and lithium battery
Patent Information
- Application Number
- CN202611220069.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0005]然而,现有技术中存在一个长期被忽视的技术问题:电解液添加剂的选择和用量往往是固定不变的,没有充分考虑不同石墨负极材料物性指标的差异
[0024]本发明将电解液添加剂与石墨负极物性指标进行匹配性设计,显著提升了锂电池的超充性能,在4C倍率下充电容量保持率达到85%以上,4C/1C下循环1000周后容量保持率不低于90%,解决了现有技术中电解液与负极材料匹配性差、超充条件下析锂严重的技术难题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to an electrolyte additive, an electrolyte, and a lithium battery. Background Technology
[0002] Lithium iron phosphate (LiFePO4, LFP) batteries have gained an increasingly important market share in the electric vehicle and energy storage sectors due to their excellent thermal safety, long cycle life, and low cost. However, the low electronic conductivity and small lithium-ion diffusion coefficient of lithium iron phosphate materials themselves mean that their supercharging performance remains lower than that of ternary lithium batteries. This has become a key bottleneck restricting the further promotion and application of LFP batteries in the high-end electric vehicle field.
[0003] In the supercharging process of lithium iron phosphate (LFP) batteries, the charging rate is limited by several steps: the diffusion of lithium ions in the positive electrode active material, the diffusion in the negative electrode active material, the transport in the electrolyte phase, and the charge transfer kinetics at the phase boundary. Among these, the negative electrode is a key area requiring attention during supercharging. During rapid charging, the process of lithium ions embedding from the electrolyte into the graphite interlayers in the graphite negative electrode requires overcoming a high energy barrier, easily leading to severe polarization, resulting in lithium metal deposition, dendrite growth, and consequently, capacity decay and safety hazards. Research indicates that lithium deposition behavior in the graphite negative electrode during high-rate charging is one of the core challenges restricting the supercharging performance of LFP batteries.
[0004] In existing technologies, improving the supercharging performance of LFP batteries mainly involves two aspects: First, focusing on the electrolyte by optimizing the solvent system, lithium salt formulation, and additive combinations to enhance ionic conductivity and form a stable SEI film. Second, modifying the graphite anode material by controlling the microstructure of graphite to improve supercharging performance. Existing technologies show that the graphitization degree, particle size, specific surface area, and compaction density of graphite have a significant impact on supercharging performance.
[0005] However, a long-neglected technical problem exists in existing technologies: the selection and dosage of electrolyte additives are often fixed, failing to fully consider the differences in the physical properties of different graphite anode materials. In reality, graphite anode materials with lower graphitization degrees have more disordered structures and defect sites, requiring higher amounts of film-forming additives for SEI film formation. They are also more prone to lithium plating under overcharge conditions, necessitating more efficient ion flux control additives. Conversely, graphite anode materials with higher graphitization degrees have more ordered layered structures, making SEI film formation relatively easier. However, excessive film-forming additives can increase interfacial resistance, negatively impacting overcharge performance. Furthermore, different graphite particle sizes significantly affect electrolyte wettability and lithium-ion transport pathways. Current technologies lack a systematic approach to matching electrolyte additives with the physical properties of graphite anodes. Summary of the Invention
[0006] Based on this, the purpose of this invention is to provide an electrolyte additive, an electrolyte, and a lithium battery. Through synergistic optimization of the electrolyte and the graphite anode material, the supercharging performance of the lithium iron phosphate battery is significantly improved, the risk of lithium plating under supercharging conditions is reduced, and the cycle life and high-temperature storage performance are also taken into account.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides an electrolyte additive, which includes a first additive, a second additive and a third additive, wherein the first additive includes a crown ether compound, the second additive includes a cyclic sulfate compound, and the third additive includes a carbonate film-forming additive.
[0008] In the electrolyte additives of this invention, crown ether compounds have a unique cavity structure, enabling them to selectively chelate transition metal ions (especially Fe) in the electrolyte. 3+ / Fe 2+ In lithium iron phosphate batteries, iron dissolution at the positive electrode is a key factor leading to capacity decay during cycling. The dissolved iron ions migrate to the negative electrode surface, catalyzing electrolyte decomposition and damaging the SEI film. Crown ethers can effectively reduce the concentration of free iron ions and block chain side reactions, while their chelating effect does not affect the Li... + Normal migration occurs. Simultaneously, cyclic sulfate compounds, acting as synergistic components, work with crown ether compounds to form a chelation-interface stabilization bifunctional system. The cyclic sulfates undergo reduction and decomposition on the negative electrode surface to generate an elastic SEI film rich in Li₂S and sulfur-containing polymers. Li₂S possesses excellent lithium-ion conductivity, significantly enhancing the lithium-ion transport rate of the SEI film. Fluorinated carbonate film-forming additives are used to form a stable and dense SEI film on the negative electrode surface.
[0009] As a further improvement of the above-mentioned solution of the present invention, the first additive accounts for 0.5% to 3% of the total mass of the electrolyte, the second additive accounts for 0.5% to 3% of the total mass of the electrolyte, and the third additive accounts for 1% to 5% of the total mass of the electrolyte.
[0010] As a further improvement to the above-described scheme of the present invention, the crown ether compound is selected from at least one of benzo-15-crown-5 (B15C5, CAS: 14098-44-3), benzo-18-crown-6 (B18C6, CAS: 14098-24-9), 4'-aminobenzo-15-crown-5 (CAS: 60835-71-4), and 4'-aminobenzo-18-crown-6 (CAS: 68941-06-0). Preferably, the crown ether compound is composed of benzo-15-crown-5 and 4'-aminobenzo-15-crown-5 in a mass ratio of 1 to 2:1. The introduction of the amino group enhances the adsorption capacity of the crown ether molecule on the graphite surface and further improves the interfacial stability.
[0011] As a further improvement to the above-described scheme of the present invention, the cyclic sulfate ester compound is selected from at least one of vinyl sulfate, divinyl sulfate, propylene sulfate, and 4-methylethylene sulfate.
[0012] As a further improvement to the above-mentioned solution of the present invention, the fluorocarbonate film-forming additive is selected from at least one of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoropropylene carbonate.
[0013] As a further improvement to the above-described scheme of the present invention, the third additive further includes at least one of vinylene carbonate, 1,3-propane sulpholactone, vinyl sulfate, and methanedisulfonate.
[0014] The present invention also provides an electrolyte comprising the electrolyte additives as described above.
[0015] As a further improvement of the above-described solution of the present invention, the electrolyte further includes a lithium salt, wherein the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium tetrafluoroborate; wherein the concentration of the lithium salt in the electrolyte is 0.8~1.5 mol / L.
[0016] As a further improvement to the above-described solution of the present invention, the electrolyte further includes a non-aqueous organic solvent, which comprises cyclic carbonates and chain carbonates, wherein the volume ratio of the cyclic carbonates to the chain carbonates is 1:2~4.
[0017] As a further improvement to the above-described scheme of the present invention, the cyclic carbonate is selected from at least one of ethylene carbonate and propylene carbonate, and the chain carbonate is selected from at least two of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0018] The present invention also provides a lithium battery comprising an electrolyte; the electrolyte comprising the electrolyte additives as described above.
[0019] As a further improvement to the above-described scheme of the present invention, the lithium battery further includes a positive electrode and a negative electrode; the active material of the positive electrode is lithium iron phosphate; the active material of the negative electrode is graphite, wherein the graphitization degree G of the graphite is ≥94% and the particle size D50 is 8~20μm, or the graphitization degree G of the graphite is 88%~93% and the particle size D50 is ≤12μm; in the electrolyte, the first additive accounts for 0.5%~3% of the total mass of the electrolyte, the second additive accounts for 0.5%~3% of the total mass of the electrolyte, and the third additive accounts for 1%~5% of the total mass of the electrolyte.
[0020] As a further improvement of the above-mentioned solution of the present invention, when the graphitization degree G of the graphite is ≥94% and the particle size D50 is 8~20μm, the first additive, the second additive, and the third additive account for m1, m2, and m3 of the total mass of the electrolyte, respectively, wherein: 0.5%≤m1<1.5%, 0.5%≤m2<2.5%, and 1%≤m3<3%.
[0021] As a further improvement of the above-mentioned solution of the present invention, when the graphitization degree G of the graphite is 88%~93% and the particle size D50≤12μm, the first additive, the second additive, and the third additive account for m1, m2, and m3 of the total mass of the electrolyte, respectively, wherein: 1.5%≤m1≤3%, 2.5%≤m2≤3%, and 3%≤m3≤5%.
[0022] This invention establishes a matching relationship between the dosage of the additive combination and the graphitization degree G of the graphite anode material. When the graphite anode meets one of the following conditions, the additive combination of this invention exhibits the best supercharging synergistic effect: Condition 1: Graphitization degree G ≥ 94% and particle size D50 is 8~20 μm; Condition 2: Graphitization degree G is 88%~93% and D50 particle size ≤ 12 μm. Specifically: When the graphitization degree G of the graphite anode material is ≥94% (high graphitization), the layered structure of graphite is highly ordered, the lithium-ion insertion / extraction channels are unobstructed, and the electronic conductivity is excellent. At this point, the main limiting factors for overcharging are the desolvation process of lithium ions at the solid-liquid interface and the impedance of the SEI film. Therefore, a low-dosage additive combination should be selected: the content of the first additive is less than 1.5 wt%, the content of the second additive is less than 2.5 wt%, and the content of the third additive is less than 3 wt%. The lower dosage of additives can form an SEI film of appropriate thickness on the ordered graphite surface, avoiding excessive film formation that leads to an increase in interfacial impedance. At the same time, an appropriate amount of crown ether-cyclic sulfate compounds are used as synergistic additives to regulate the interfacial stability at high rates.
[0023] When the graphitization degree G of the graphite anode material is 88%~93% (medium graphitization) and the particle size D50 ≤ 12μm (small particle size), the graphite material has more disordered structure and defect sites. However, the small particle size shortens the solid-phase diffusion distance of lithium ions, which is beneficial for overcharging. Such graphite anodes require more complete SEI film formation and stronger lithium plating control during overcharging. Therefore, a high-dosage additive combination should be selected: the content of the first additive is 1.5wt%~3wt%, the content of the second additive is 2.5wt%~3wt%, and the content of the third additive is 3wt%~5wt%. Higher dosages of additives can fully cover the defect sites on the graphite surface, forming a stable and uniform SEI film; higher dosages of crown ether-cyclic sulfate compounds as synergistic additives can effectively control the lithium-ion flux and lithium plating behavior during overcharging.
[0024] This invention designs a matching system between electrolyte additives and graphite anode properties, significantly improving the overcharge performance of lithium batteries. At 4C, the capacity retention rate reaches over 85%, and after 1000 cycles at 4C / 1C, the capacity retention rate is no less than 90%. This solves the technical problems of poor matching between electrolyte and anode materials and severe lithium plating under overcharge conditions in the prior art.
[0025] As a further improvement to the above-described scheme of the present invention, the specific surface area of the graphite is 0.8~4.0 m². 2 / g, compacted density is 1.4~1.8 g / cm³ 3 .
[0026] As a further improvement to the above-mentioned solution of the present invention, the graphite is at least one of artificial graphite and natural graphite.
[0027] This invention utilizes a synergistic combination of crown ether compounds and cyclic sulfate compounds as first and second additives, combined with a third additive, a fluorocarbonate film-forming additive. The additive dosage is designed to match the graphitization degree and particle size D50 of the graphite anode material. The elastic SEI film constructed through the crown ether-cyclic sulfate synergistic additives transforms irreversible lithium deposition into reversible utilization. Even if a small amount of lithium is deposited during overcharging, the rapid ion flux and stress mitigation capability of the elastic SEI film ensure uniform deposition and highly reversible re-embedding of the deposited lithium into the graphite interlayer, thereby avoiding lithium dendrite growth and the formation of dead lithium. This achieves synergistic optimization of the electrolyte and anode material, significantly improving the overcharging performance of lithium iron phosphate batteries, reducing the risk of lithium deposition under overcharging conditions, and simultaneously ensuring cycle life and high-temperature storage performance. Detailed Implementation
[0028] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0030] The specific physical properties of the graphite anode materials used in the following embodiments and comparative examples are shown in Table 1 below: Table 1 Physical properties of graphite anode materials
[0031] The above-mentioned raw materials are only used to illustrate the physical properties of the graphite anode material used in the experiments of this invention, so as to fully disclose them, and do not mean that the invention cannot be achieved by using graphite anode materials with other physical properties.
[0032] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.
[0033] Example 1 This embodiment proposes a lithium iron phosphate battery, the preparation method of which is as follows: S1. Electrolyte Preparation The electrolyte in this embodiment is composed of lithium hexafluorophosphate (LiPF6), a non-aqueous organic solvent, and additives, wherein: the concentration of lithium hexafluorophosphate is 1.1 mol / L; the additives include a first additive, a second additive, and a third additive, wherein the first additive is benzo-15-crown-5 (B15C5) and its addition amount accounts for 0.5% of the total mass of the electrolyte; the second additive is ethylene disulfate (BiDTD) and its addition amount accounts for 1% of the total mass of the electrolyte; the third additive is fluoroethylene carbonate (FEC) and its addition amount accounts for 1% of the total mass of the electrolyte; the balance is a non-aqueous organic solvent, which is composed of ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) in a volume ratio of 30:20:50.
[0034] The electrolyte is prepared as follows: In an argon glove box (moisture content <1 ppm, oxygen content <1 ppm), lithium hexafluorophosphate, non-aqueous organic solvent and additives are mixed and stirred until completely dissolved to obtain the electrolyte.
[0035] S2. Assemble lithium iron phosphate superchargeable batteries Preparation of positive electrode sheet: LiFePO4, carbon nanotube conductive agent and PVDF binder are mixed evenly in a mass ratio of 97:2:1 to obtain positive electrode slurry; the positive electrode slurry is coated on aluminum foil current collector, dried, rolled, slit and cut, and then dried in a vacuum drying oven at 85℃ for 4h to obtain positive electrode sheet. Preparation of negative electrode sheet: Graphite (G-1), conductive carbon black, thickener (CMC, carboxymethyl cellulose) and binder (styrene-butadiene latex, SBR) are mixed evenly in a mass ratio of 94.5:2:1.5:2 to obtain negative electrode slurry; the negative electrode slurry is coated on copper foil current collector, dried, cold pressed, slit, and cut, and then dried in a vacuum drying oven at 85℃ for 4 hours to obtain negative electrode sheet; Preparation of lithium iron phosphate batteries: Positive and negative electrode sheets are assembled together in a stacked structure, separated by a separator (PE composite alumina separator) to obtain a bare cell. This cell is then wrapped with a 150μm thick aluminum-plastic film and dried in a vacuum drying oven at 85℃ for 48 hours to obtain a dry cell. The electrolyte prepared in step S1 is then injected and the cell is sealed. The N / P ratio of the assembled cell is 1.1, and the electrolyte injection coefficient is 4G / Ah. After formation, aging, and capacity testing, a lithium iron phosphate superchargeable battery with a rated capacity of 1.8Ah is obtained.
[0036] Example 2 The difference between this embodiment and Embodiment 1 is as follows: In the electrolyte of this embodiment, the additives include a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5 and 4'-aminobenzo-15-crown-5 (NH2-B15C5), with the amount of benzo-15-crown-5 accounting for 0.6% of the total mass of the electrolyte, and the amount of 4'-aminobenzo-15-crown-5 accounting for 0.6% of the total mass of the electrolyte. The second additive is ethylene disulfate (BiDTD) and its amount accounts for 1.2% of the total mass of the electrolyte. The third additive is fluoroethylene carbonate (FEC) and its amount accounts for 2% of the total mass of the electrolyte. The graphite used in the negative electrode sheet of this embodiment is designated as G-2.
[0037] Example 3 The difference between this embodiment and Embodiment 1 is that the electrolyte in this embodiment contains additives including a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5, and its addition amount accounts for 1.5% of the total mass of the electrolyte. The second additive is ethylene disulfate (BiDTD), and its addition amount accounts for 2.5% of the total mass of the electrolyte. The third additive is fluoroethylene carbonate (FEC) and vinylene carbonate (VC), with FEC accounting for 3.5% of the total mass of the electrolyte and VC accounting for 1% of the total mass of the electrolyte. The graphite used in the negative electrode sheet in this embodiment is designated as G-3.
[0038] Example 4 The difference between this embodiment and Embodiment 1 is as follows: In the electrolyte of this embodiment, the additives include a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5 and 4'-aminobenzo-15-crown-5, with the amount of benzo-15-crown-5 accounting for 0.9% of the total mass of the electrolyte, and the amount of 4'-aminobenzo-15-crown-5 accounting for 0.9% of the total mass of the electrolyte. The second additive is ethylene disulfate (BiDTD), and its amount accounts for 3% of the total mass of the electrolyte. The third additive is fluoroethylene carbonate (FEC) and 1,3-propane sulpholactone (PS), with the amount of FEC accounting for 4% of the total mass of the electrolyte and the amount of PS accounting for 0.8% of the total mass of the electrolyte. The graphite used in the negative electrode sheet of this embodiment is designated as G-4.
[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that the electrolyte in this comparative example contains additives including a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5, and the amount of benzo-15-crown-5 added accounts for 1% of the total mass of the electrolyte. The second additive is ethylene disulfate (BiDTD), and its amount accounts for 2.5% of the total mass of the electrolyte. The third additive is fluoroethylene carbonate (FEC), and its amount accounts for 2.5% of the total mass of the electrolyte.
[0040] Comparative Example 2 The difference between this comparative example and Example 1 is that: in the electrolyte of this comparative example, the additive is fluoroethylene carbonate (FEC) and its addition amount accounts for 3% of the total mass of the electrolyte; the graphite used in the negative electrode sheet of this comparative example is numbered G-2.
[0041] Comparative Example 3 The difference between this comparative example and Example 1 is that the electrolyte in this comparative example contains additives including a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5 and its addition amount accounts for 1% of the total mass of the electrolyte; the second additive is ethylene disulfate (BiDTD) and its addition amount accounts for 2.5% of the total mass of the electrolyte; the third additive is fluoroethylene carbonate (FEC) and its addition amount accounts for 2.5% of the total mass of the electrolyte; the graphite used in the negative electrode sheet of this comparative example is designated as G-3.
[0042] Comparative Example 4 The difference between this comparative example and Example 1 is that the electrolyte in this comparative example contains additives including fluoroethylene carbonate (FEC) and vinylene carbonate (VC), with FEC accounting for 4% of the total mass of the electrolyte and VC accounting for 1% of the total mass of the electrolyte; the graphite used in the negative electrode sheet of this comparative example is designated as G-4.
[0043] Comparative Example 5 The difference between this comparative example and Example 1 is as follows: In the electrolyte of this comparative example, the additives include a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5, and its addition amount accounts for 1.5% of the total mass of the electrolyte; the second additive is ethylene disulfate (BiDTD), and its addition amount accounts for 2.5% of the total mass of the electrolyte; the third additive is fluoroethylene carbonate (FEC) and vinylene carbonate (VC), with FEC accounting for 3.5% of the total mass of the electrolyte and VC accounting for 1% of the total mass of the electrolyte; the graphite used in the negative electrode sheet of this comparative example is designated as G-5.
[0044] Comparative Example 6 The difference between this comparative example and Example 1 is as follows: In the electrolyte of this comparative example, the additives include a first additive, a second additive, and a third additive. The first additive is benzo-15-crown-5 and 4'-aminobenzo-15-crown-5, with the amount of benzo-15-crown-5 and 4'-aminobenzo-15-crown-5 accounting for 0.9% of the total mass of the electrolyte. The second additive is ethylene disulfate (BiDTD) accounting for 3% of the total mass of the electrolyte. The third additive is fluoroethylene carbonate (FEC) and 1,3-propane sulpholactone (PS), with the amount of FEC and PS accounting for 4% and 0.8% of the total mass of the electrolyte, respectively. The graphite used in the negative electrode of this comparative example is designated as G-6.
[0045] The electrolyte additive compositions of Examples 1-4 and Comparative Examples 1-6 are shown in Table 2.
[0046] Table 2 Electrolyte Additive Composition (Based on Total Mass of Electrolyte)
[0047] Test case The following electrical performance tests were performed on the batteries obtained in Examples 1-4 and Comparative Examples 1-6: (1) Supercharging performance test Under constant temperature conditions of 25℃, the battery was charged at a constant current and constant voltage of 0.33C to 3.65V, with a cutoff at 0.05C. It was then discharged at a constant current of 0.33C to 2.5V, and this cycle was repeated three times to obtain the initial capacity. Subsequently, charging tests were conducted at constant currents of 2C, 3C, 4C, and 5C, charging to 3.65V and then maintaining a constant voltage until the cutoff at 0.05C. The charging capacity at each rate was recorded. Using the 0.33C discharge capacity as a benchmark, the capacity retention rate at each rate was calculated.
[0048] (2) High-temperature storage performance test Under constant temperature conditions of 25℃, the battery was charged at a constant current and constant voltage of 0.33C to 3.65V, with a cutoff at 0.05C. Then, it was discharged at a constant current of 0.33C to 2.5V, repeated three times. The discharge capacity of the last cycle was recorded as C0. Then, the battery was fully charged again at a constant current and constant voltage of 0.33C to 3.65V, with a cutoff at 0.05C. After placing the battery in a 60℃ oven for 7 days, it was discharged again at a constant current of 0.33C to 2.5V, then charged again at a constant current and constant voltage of 0.33C to 3.65V, with a cutoff at 0.05C, repeated three times. The first discharge capacity was recorded as C1, and the last discharge capacity as C2. Storage capacity retention rate = C1 / C0, storage capacity recovery rate = C2 / C0. The internal resistance before and after storage was tested, and the internal resistance growth rate was calculated as R1 / R0, where R1 and R0 represent the battery's internal resistance before and after storage, respectively.
[0049] (3) Overcharging and cycling performance The capacity retention rate of each battery at different charging rates and the capacity retention rate after 1000 cycles under 4C charging / 1C discharging conditions were recorded. After the cycle test, the batteries were disassembled in an argon glove box under full charge, the negative electrode was removed, cleaned with DMC, and the surface lithium plating was observed.
[0050] The test results are shown in Tables 3 and 4.
[0051] Table 3 Electrical performance test results
[0052] Table 4 Performance retention rate of each battery after 7 days of storage at 60℃
[0053] The results in Tables 3 and 4 show that: The batteries prepared in Examples 1-4 of this invention exhibit significantly higher capacity retention rates at 4C and 5C rates compared to Comparative Examples 1-6. For example, Example 1 (G-1 matched with E-1) achieved a capacity retention rate of 90.3% at 4C and 86.5% at 5C; while Comparative Example 1, using the same graphite anode but with different additive dosage formulations, only achieved a capacity retention rate of 83.4% at 4C and only 76.8% at 5C. This demonstrates that the matching of additives with graphite properties significantly improves supercharging performance.
[0054] For Comparative Example 5 (G-5, graphitization degree of 89.5%, particle size of 18.5 μm) and Comparative Example 6 (G-6, graphitization degree of 86.2%, particle size of 11.8 μm), even though the additive combinations of Examples 3 and 4 of the present invention were used respectively, the supercharging performance was significantly lower than that of the batteries of Examples 3 and 4 because the graphite anode material itself did not meet the physical property requirements. This also confirms the importance of the screening conditions for graphite physical property in the present invention.
[0055] The batteries with matched additive and graphite properties (Examples 1-4) maintained a capacity retention of over 90% after 1000 cycles, while the batteries in the comparative examples generally retained less than 85%. Disassembly of the fully charged negative electrode interface revealed that the batteries with matched additive and graphite properties exhibited only slightly and uniformly distributed lithium deposits on the negative electrode surface, with no obvious dendrites observed. In contrast, the negative electrodes of Comparative Examples 5 and 6, where the additive and graphite properties were not matched, showed severe lithium dendrite growth, which is consistent with the rapid capacity decay observed during the supercharge test.
[0056] Batteries with additives and graphite property matching schemes (Examples 1-4) maintained a capacity retention rate of over 92% and a capacity recovery rate of over 94% after 7 days of storage at 60°C, with the internal resistance growth rate controlled within 15%. This is attributed to the effective chelation of iron ions by crown ether compounds, which suppressed the side reaction of iron ion-catalyzed electrolyte decomposition at high temperatures. Simultaneously, the SEI film formed by the synergistic effect of FEC and crown ether-BiDTD exhibits excellent thermal stability.
[0057] Example 1 uses a graphite anode G-1 with high graphitization (G=95.2%) and small particle size (D50=14.8μm) matched with a low-dose additive formulation E-1. Under 4C supercharge conditions, the battery exhibits excellent charge capacity retention (90.3%) and cycle stability (91.5% after 1000 cycles), as well as good high-temperature storage performance. This demonstrates that for graphite with high graphitization, a low dose of film-forming additives can form a sufficiently dense and stable SEI film, avoiding the adverse effects of excessive additives on ion transport.
[0058] Example 2 uses a graphite anode G-2 with high graphitization (G=94.5%) and small particle size (D50=11.5μm) matched with a modified low-dose additive formulation E-2 (a combination of B15C5 and NH2-B15C5). Compared with Example 1, this scheme further improves the charging capacity retention at 4C and 5C (87.3% vs 86.5% at 5C), and has a higher capacity retention after 1000 cycles (92.3% vs 91.5%). This indicates that the introduction of amino groups enhances the interfacial adsorption capacity of crown ether molecules and improves the stability of the SEI film.
[0059] Example 3 uses a graphite anode G-3 with medium graphitization (G=92.1%) and small particle size (D50=10.2μm) matched with a high-dose additive formulation E-3. Although the graphitization degree is lower than that of Examples 1 and 2, due to the use of a high-dose additive combination, the charging capacity retention rate at 4C still reaches 88.6%, and the cycle retention rate after 1000 cycles is 90.8%, which is basically equivalent to the high graphitization scheme. This verifies the effectiveness of the matching strategy of the present invention: the disadvantage of insufficient order in the graphite structure is compensated for by increasing the dosage.
[0060] Example 4 uses natural graphite G-4 (G=90.8%, D50=8.6μm) matched with a high-dose additive formulation E-4. Natural graphite has a higher specific surface area (2.5 μm). 2 The presence of more surface defects (such as ' / G') necessitates stronger SEI film protection. Test results show that the natural graphite battery with the matching scheme achieves excellent supercharge performance (87.9% at 4C) and cycle performance (91.2% after 1000 cycles), indicating that the matching scheme of this invention is applicable to different types of graphite.
[0061] Comparative Example 1 uses the same graphite anode G-1 as Example 1, but uses a general additive formulation E-7 (not matched according to the degree of graphitization). Since the additive content in the general formulation is between low and high dosage, it is too high for graphite with a high degree of graphitization, resulting in an excessively thick SEI film, increased interfacial impedance, and a 4C charging capacity retention rate of only 83.4% and a 1000-cycle retention rate of only 84.2%.
[0062] Comparative Example 2 used the same graphite anode G-2 as Example 2, but only 3.0% FEC was used as an additive (without crown ether-BiDTD synergistic component). The results showed a significant decrease in overcharge and cycling performance, with only 82.1% at 4C and only 83.5% after 1000 cycles. This demonstrates the crucial role of the crown ether-BiDTD synergistic additive under overcharge conditions, and that the traditional SEI film formed by FEC alone is insufficient to effectively control lithium plating behavior during the overcharge process.
[0063] Comparative Example 3 used the same graphite anode G-3 as Example 3, but used the general additive formulation E-7. The results showed that the 4C charging capacity retention rate was only 81.5%, far lower than the 88.6% of Example 3. This indicates that graphite with medium graphitization is more sensitive to the additive ratio, and matching design is crucial.
[0064] Comparative Example 4 used the exact same graphite anode G-4 as Example 4, but only used 4% FEC + 1% VC as additives. The capacity retention rate at 4C charging was only 80.3%, at 5C only 72.1%, and after 1000 cycles of 4C / 1C, the capacity retention rate was only 82.6%. The anode surface showed moderately heavy lithium deposition, further demonstrating the key role of crown ether-BiDTD synergistic additives in natural graphite systems with medium graphitization, small particle size, and high specific surface area.
[0065] Comparative Example 5 used a graphite anode G-5 with medium graphitization (G=89.5%, D50=18.5μm). Although the graphitization was in the range of 88%~93%, the particle size was relatively large (>12μm). Even with the use of a high-dose additive formulation E-3, the overcharge performance was still poor (4C 75.8%, 5C 65.3%), and the capacity retention after 1000 cycles was only 76.5%, with severe lithium plating on the anode surface. This indicates that for graphite with medium graphitization, a small particle size (≤12μm) is a necessary condition to realize the matching advantages.
[0066] Comparative Example 6 used a low-graphitization graphite anode, G-6 (G=86.2%, D50=11.8μm). While the particle size met the requirements, the graphitization was too low. Even with a high-dose additive formulation E-4, the overcharge and cycle performance was still unsatisfactory, with a 4C charge retention rate of only 72.6% and a 1000-cycle retention rate of 73.8%, indicating severe lithium plating on the anode. This demonstrates that when the graphitization is too low, the structural order of graphite itself is insufficient to support overcharge applications, and this cannot be compensated for solely by electrolyte additives.
[0067] The results of the above embodiments and comparative examples fully demonstrate that the present invention can significantly improve the supercharging performance and cycle stability of lithium iron phosphate batteries by combining sieved crown ether-BiDTD synergistic additives with fluorinated carbonate film-forming additives and designing them in a matching manner according to the graphitization degree G and particle size D50 of the graphite anode material.
[0068] For highly ordered graphite with a graphitization degree G≥94% and a D50 of 8~20μm, the best matching effect can be obtained by using a low-dose additive combination (0.5%~1.5% of the first additive and 1%~2.5% of the second additive), with a 4C charging capacity retention rate ≥90% and a 1000-cycle retention rate ≥91%.
[0069] For medium-order small-particle-size graphite with a graphitization degree G of 88%~93% and D50≤12μm, the best matching effect can be obtained by using a high-dose additive combination (1.5%~3.0% for the first additive and 2.5%~3% for the second additive), with a 4C charging capacity retention rate ≥87% and a 1000-cycle retention rate ≥90%.
[0070] When the graphitization degree G of the graphite anode material is less than 88% or the particle size D50 of medium-graphitized graphite is greater than 12 μm, even with the additive combination of the present invention, the overcharging performance is difficult to reach the ideal level, indicating that the physical properties of the anode material itself are a necessary prerequisite for the effective implementation of the matching scheme of the present invention.
[0071] The matching design of this invention breaks the conventional thinking of applying a one-size-fits-all approach to electrolyte additives in the prior art, and provides a brand-new technical solution for the precise design of supercharged electrolytes for lithium iron phosphate batteries, which has significant technological progress and industrial application value.
[0072] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0073] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. An electrolyte additive, characterized in that, It includes a first additive, a second additive, and a third additive; the electrolyte additive is used in lithium iron phosphate batteries, wherein the active material of the positive electrode of the lithium iron phosphate battery is lithium iron phosphate and the active material of the negative electrode is graphite; the first additive includes crown ether compounds, the second additive includes cyclic sulfate compounds, and the third additive includes fluorocarbonate film-forming additives. The first additive, the second additive, and the third additive account for m1, m2, and m3 of the total mass of the electrolyte, respectively; when the graphitization degree G of the graphite is ≥94% and the particle size D50 is 8~20μm, 0.5%≤m1<1.5%, 0.5%≤m2<2.5%, and 1%≤m3<3%; when the graphitization degree G of the graphite is 88%~93% and the particle size D50 is ≤12μm, 1.5%≤m1≤3%, 2.5%≤m2≤3%, and 3%≤m3≤5%.
2. The electrolyte additive according to claim 1, characterized in that, The crown ether compound is selected from at least one of benzo-15-crown-5, benzo-18-crown-6, 4'-aminobenzo-15-crown-5, and 4'-aminobenzo-18-crown-6.
3. The electrolyte additive according to claim 1, characterized in that, The cyclic sulfate ester compound is selected from at least one of vinyl sulfate, divinyl sulfate, propylene sulfate, and 4-methylethylene sulfate.
4. The electrolyte additive according to claim 1, characterized in that, The fluorocarbonate film-forming additives are selected from at least one of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoropropylene carbonate.
5. The electrolyte additive according to claim 1, characterized in that, The third additive also includes at least one of vinylene carbonate, 1,3-propanesulfonyl lactone, and methylene disulfonate.
6. An electrolyte, characterized in that, It includes the electrolyte additive as described in any one of claims 1-5.
7. The electrolyte according to claim 6, characterized in that, The electrolyte further includes a lithium salt, which is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium tetrafluoroborate; the concentration of the lithium salt in the electrolyte is 0.8~1.5 mol / L.
8. The electrolyte according to claim 6, characterized in that, The electrolyte also includes a non-aqueous organic solvent, which comprises cyclic carbonates and chain carbonates, wherein the volume ratio of the cyclic carbonates to the chain carbonates is 1:2 to 4.
9. The electrolyte according to claim 8, characterized in that, The cyclic carbonate is selected from at least one of ethylene carbonate and propylene carbonate, and the chain carbonate is selected from at least two of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
10. A lithium battery comprising an electrolyte; characterized in that, The electrolyte includes the electrolyte additive as described in any one of claims 1-5.
11. The lithium battery according to claim 10, characterized in that, The specific surface area of the graphite is 0.8~4.0 m². 2 / g, compacted density is 1.4~1.8 g / cm³ 3 .
12. The lithium battery according to claim 10, characterized in that, The graphite is at least one of artificial graphite and natural graphite.
Citation Information
Patent Citations
Quick charge type lithium ion battery electrolyte and application thereof
CN118970171A
Electrolyte for high-nickel ternary lithium battery
CN121484214A
